Fine grains within narrow temperature range by tuning strain-induced boundary migration dominated recrystallization for selective laser melted Inconel 718 - Chen, Kewei (2022)
In this study, fine grains are achieved with weak texture of selective laser melted Inconel 718 (SLM IN718) if annealed within a narrow temperature range (1,070 ∼ 1,090 °C), while abnormal grain growth (AGG) is induced if annealed at temperature higher than that range, resulting in large matrix grains and twins. By a novel quasi-in-situ electron backscatter diffraction (EBSD) method, the recrystallization of SLM IN718 is primarily dominated by strain-induced boundary migration (SIBM) at 1,150 or 1,075 °C via statistical analysis. In particular, AGG at 1,150 °C is attributed to quick consumption of the high-strain regions due to a higher grain boundary (GB) velocity, while fine grains at 1,075 °C attributed to activation of more SIBM grains and uniform growth of these grains due to a slower GB velocity. The techniques proposed in this study can also work well for other SLM face-centered cubic alloys.